Production, characterization and kinetic model of biosurfactant produced by lactic acid bacteria (2021)
Biosurfactants are surface active molecules produced by microorganisms which have the ability to disrupt the plasma membrane. Biosurfactant properties are important in the food, pharmaceutical and oil industries. Lactic acid bacteria can produce cell-bound and excreted biosurfactants. Results: The biosurfactant-producing ability of three Lactobacillus strains was analyzed, and the effects of carbon and nitrogen sources and aeration conditions were studied. The three species of lactobacillus evaluated were able to produce biosurfactants in anaerobic conditions, which was measured as the capacity of one extract to reduce the surface tension compared to a control. The decreasing order of biosurfactant production was L. plantarum>Lactobacillus sp.>L. acidophilus. Lactose was a better carbon source than glucose, achieving a 23.8% reduction in surface tension versus 12.9% for glucose. Two complex nitrogen sources are required for growth and biosurfactant production. The maximum production was reached at 48 h under stationary conditions. However, the highest level of production occurred in the exponential phase. Biosurfactant exhibits a critical micelle concentration of 0.359 ± 0.001 g/L and a low toxicity against E. coli. Fourier transform infrared spectroscopy indicated a glycoprotein structure. Additionally, the kinetics of fermentation were modeled using a logistic model for the biomass and the product, achieving a good fit (R2 > 0.9). Conclusions: L. plantarum derived biosurfactant production was enhanced using adequate carbon and nitrogen sources, the biosurfactant is complex in structure and because of its low toxicity could be applied to enhance cell permeability in E. coli.